Enhancing Customer Service Performance through Technological Integration, Human Capital Development, and Multi-Channel Operations:: An Operations Management Perspective - Andi Irsandi Yusri; Abdul Haris; Anan Chaiyasit (Vifada Management and Social Sciences, 2024)
This study investigates effective customer service improvement strategies within an operations management framework, with particular emphasis on technological integration, employee capability development, multi-channel service systems, and systematic utilization of customer feedback. A mixed-methods research design was employed to ensure methodological rigor, combining quantitative survey data and qualitative interview insights. The sample comprised 200 customer service managers and frontline employees representing diverse industry sectors. Quantitative data were analyzed using descriptive and inferential statistical techniques, while qualitative data were examined through thematic analysis to capture deeper operational perspectives. The findings demonstrate that the integration of artificial intelligence and customer relationship management (CRM) systems significantly enhances service efficiency, responsiveness, and overall customer satisfaction. Furthermore, comprehensive and continuous employee training emerges as a critical enabler for maximizing technological benefits and addressing increasingly complex customer expectations. The study also highlights that effective multi-channel service delivery depends on platform integration and employee readiness to ensure service consistency across touchpoints. Additionally, the strategic collection and application of customer feedback play a vital role in strengthening customer trust, loyalty, and long-term engagement. Importantly, aligning customer service initiatives with broader organizational objectives enhances strategic coherence and operational performance. This study offers a holistic and empirically grounded framework for improving customer service operations, contributing valuable insights to both academic discourse and managerial practice in contemporary service management.